Parkinsonism as a Manifestation of Neuropsychiatric Systemic Lupus Erythematosus: A Case Report and Literature Review - Qi TANG,; Jing WANG,; Jinwei CHEN,; Xi XIE,; Jing TIAN, (Archives of Rheumatology, 2015)
Involvement of the central nervous system in systemic lupus erythematosus has been well documented. Parkinsonism as a manifestation of central nervous system lupus is rare. In this article, we report a 17-year-old girl who developed parkinsonism within one month of the onset of systemic lupus erythematosus, and presented with expressionless facies, bradykinesia, marked rigidity, and hypermyotonia. Magnetic resonance imaging showed abnormity in bilateral basal ganglia, external capsule, insular lobe, and lateral hippocampus symmetrically. Methylprednisolone pulse therapy, intravenous cyclophosphamide, and intrathecal injection of methotrexate plus dexamethasone were prescribed. Two months later, the patient returned with complete clinical recovery of neuropsychiatric symptoms and signs.